REPRESENTASI NASIONALISME DALAM IKLAN KORPORAT PT. GUDANG GARAM TBK - Wibisono, Ria Angelia (Institute of Research and Community Outreach - Petra Christian University, 2008)
Representation of Nationalism in Corporate Advertising of PT. Gudang Garam Tbk. Nationalism is a psychological condition in which somebody surrenders his loyalty to nation state in the name of a nation. While representation is something refers to message, by which reality is encoded in communication; by words, sound, image, or their combination. This thesis explains about how nationalism is represented in the corporate advertising of PT.Gudang Garam Tbk. version â€œRumahku Indonesiakuâ€ and â€œRumahku Indonesiaku: Cahaya Asaâ€. This is a qualitative research using semiotics method, based on the codes of television theory by John Fiske, syntagm-paradigm concept by Saussure, and the grammar of film and television. The nationalism represented in the advertising consists of self-determination, solidarity, patriotism, social justice, and national identity. Although the advertising is a Corporate Social Responsibility campaign, it still contains particular symbol refers to usual symbol that represents Gudang Garam cigarette product.